Sound branch cash management for less: A low-cost forecasting algorithm under uncertain demand - García Cabello, Julia; Lobillo, F.J. (Omega (Oxford), 2017)
This paper deals with cash management for bank branches, under the assumption that branches have a role to play in the improvement of global bank institution performance. In the current scenario of unprecedented pressure amongst banks to keep costs under control, our contribution is the design of a sound and low-cost algorithm to optimize branch cash holdings using software implementation in SageMath. It is accompanied by data processing based on 60,000 real banking records. This is the first academic paper to run such an extensive database at branch level. We find that our algorithm by and large performs well when forecasting the cash amounts that the branch might require from the central hub to satisfy all branch necessities, avoiding the generation of either surplus or shortage of cash. It is also extremely easy to implement in daily branching practice, leading to an overall reduction in operating costs. In addition, our algorithm may be easily adjusted as required and be tailor-made to the special requirements of each banking institution. •We design a sound and low-cost algorithm which optimizes branch cash holdings.•Our algorithm may be easily adjusted as required and be tailor-made for each banking institution.•We test the accuracy of our algorithm with data processing on 60,000 real banking records.•This is the first academic paper to run such an extensive database at branch level.•Our software may significantly improve branch cash management processes.